Control of electronic business transactions - between the enshrinement of safeguards and the establishment of ethics – (El-Wahat Journal for Research and Studies, 2023)
Abstract:Algerian legislator, like the comparative legislation on electronic commerce in Act No. 18-05, has regulated electronic business transactions. In this study, we explained the legal protection of the electronic consumer while highlighting the rules of ethics of electronic commerce, and then we mentioned the various legal safeguards dedicated to consumer protection before and after the implementation of the electronic contract, focusing on the importance of control in various forms of such practices. We have reached several results, the most important of which is the lack of awareness of the electronic consumer given that the responsible agencies that deal with the issue of his protection have not yet risen to the seriousness of their role, and their programs and methods of awareness and education have not reached the level of importance of this issue.Keywords: Electronic Commerce - Legal Protection - Electronic Consumer - Ethical Rules – Control bodies.